Long-term organic farming impact on soil nutrient status and grain yield at the foothill of Himalayas - Singh, Pranjali; Suyal, Deep Chandra; Kumar, Saurabh; Singh, Dhananjay Kumar; Goel, Reeta (Frontiers in Environmental Science, 2024)
This study aimed to document the effects of long-term organic farming (OF) impact on the soil quality, agronomical parameters, crop productivity and food grain yield compared to conventional farming system (CF). The crop in this study was chickpea (Cicer arietinum) and the field was located at Pantnagar, India in the foothills of Himalayas. Organic farming approach involved utilizing a blend of farmyard manure and vermicompost, combined with a biopesticide comprising neem oil and cow urine. Chickpea grain micronutrient analysis was done using Atomic Absorption Spectrophotometer. It was found that the soil physico-chemical properties of the organic plot were improved over the conventional partner. At the postharvesting stage, organically managed field had higher soil organic carbon than conventional field (OF-0.93± 0.05%, CF-0.75± 0.12%), higher available nitrogen (OF-317± 11 kg/ha, CF-240± 22 kg/ha) as well as more available phosphorus (OF-37.4± 1.3kg/ha, CF-25.2± 2.5 kg/ha).The agronomical parameters of chickpea crop were better under organic cultivation with significantly high nodule number, nodule dry weight and grains per pod. Hence the grain yield of the crop was better under organic cultivation with the yield of 1048 kg ha -1 whereas it was 896.5kg ha -1 for conventional plot. The Fe and Zn content of organically produced chickpea grains were almost double of their conventional counterpart. Therefore, organic cultivation led to better soil fertility, chickpea grains yield, and nutrient status of the crop. It will be beneficial for the nutritious and sustainable production of chickpea in Himalayan regions.